Evaluating Operational Effects of Bus Lane with Intermittent Priority under Connected Vehicle Environments - Dingxin Wu; Wei Deng; Yan Song; Jian Wang; Dewen Kong (Discrete Dynamics in Nature and Society)
Bus lane with intermittent priority (BLIP) is an innovative method to improve the reliability of bus services while promoting efficient usage of road resources. Vehicle-to-vehicle (V2V) communication is an advanced technology that can greatly enhance the vehicle mobility, improve traffic safety, and alleviate traffic jams. To explore the benefits of BLIP operation under a connected environment, this study proposed a three-lane cellular automata (CA) model under opening boundary condition. In particular, a mandatory BLIP lane-changing rule is developed to analyze special asymmetric lane-changing behaviors. To improve the simulation accuracy, a smaller cell size is used in the CA model. Through massive numerical simulations, the benefits and influences of BLIP are explored in this paper. They include impacts on neighborhood lanes such as traffic density increasing and average speed decreasing, lane-changing behaviors, lane usage, and the impacts of bus departure interval and clear distance on the road capacity of BLIP. Analysis of traffic flow characteristics of BLIP reveals that there is a strong relationship among bus departure interval, clear distance, and road capacity. Furthermore, setting conditions for deployment of BLIP under the V2V environment such as reasonable departure interval, clear distance, and traffic density are obtained.